Taxonomy of scaly crickets (Orthoptera: Mogoplistidae: Mogoplistinae) from China: five new species groups and three new species of the genus Ornebius Guérin-Méneville, 1844 - He, Zhixin; Ma, Ge; Long, Jifeng; Wang, Yan; Zhang, Tao; Ma, Libin (Zootaxa, 2021)
The genus Ornebius Guérin-Méneville, 1844 was divided into five species groups based on the structure of the male genitalia. Three new species of Ornebius were described from the Chinese provinces of Hainan, Guangxi and Guangdong. Type specimens are deposited at the Museum of Flora and Fauna of Shaanxi Normal University, Xi’an, China (SNNU).